2012
DOI: 10.3109/0284186x.2012.689853
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison between VMAT with different dose calculation algorithms and protons for soft-tissue sarcoma radiotherapy

Abstract: (2013) Dosimetric comparison between VMAT with different dose calculation algorithms and protons for soft-tissue sarcoma radiotherapy, Acta Oncologica, 52:3, 545-552,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…Such difference is of essential importance for dose in bone. Fogliata et al (35) compared the two types of AXB calculation with AAA in VMAT treatment plans for leg sarcoma cases and found that dose‐to‐water scheme on average overestimate dose in bone by 5% compared to dose‐to‐medium and AAA. In theory, the dose‐to‐medium calculation better reflects the physical cross sections of the photon and electron interactions with matter, and has shown to have better agreement with conventional “rescaled‐to‐water” calculation (AAA and CCC) (21) …”
Section: Discussionmentioning
confidence: 99%
“…Such difference is of essential importance for dose in bone. Fogliata et al (35) compared the two types of AXB calculation with AAA in VMAT treatment plans for leg sarcoma cases and found that dose‐to‐water scheme on average overestimate dose in bone by 5% compared to dose‐to‐medium and AAA. In theory, the dose‐to‐medium calculation better reflects the physical cross sections of the photon and electron interactions with matter, and has shown to have better agreement with conventional “rescaled‐to‐water” calculation (AAA and CCC) (21) …”
Section: Discussionmentioning
confidence: 99%
“…Kan et al 34 reported that, in comparison to the AXB_Dm, the AXB_Dw will calculate higher mean PTV doses by up to 4% and higher mean doses to the tissues adjacent to bone by up to about 2% for nasopharygeal carcinoma. Fogliata et al 35 reported that the dose distributions calculated by the AXB_Dw were about 5% higher than corresponding ones calculated by the AXB_Dm for soft-tissue sarcoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The only DVH parameter value for OARs that was predicted to be higher by the AXB10 was the maximum lung dose. Fogliata et al 56 performed a dosimetric comparison between the AXB11, the AAA and proton radiotherapy for soft-tissue sarcoma. No clear differences were observed in the PTV dose distributions between the AXB11 and the AAA, though the number of needed monitor units by the AXB11 was 1.8% higher.…”
Section: The Axb Algorithm and Patient Plansmentioning
confidence: 99%